Campaña de lanzamiento de producto para la bebida energizante Boom Power - Cárdenas Mesia, Arantxa De María (2023)
The project focuses on the development of the launching campaign of Boom Power, a new brand in the category of energy drinks that is entering the market with a new product that contains maca, guarana, ginseng, theine, caffeine, taurine, and is sweetened with natural yacon extract. The marketing goal of the launching campaign is to achieve 12% market share by the end of the first year of operations. After investigating the national context, the product’s category and the target audience, it was possible to identify the insights of the target audience and see how their lifestyle influences the decision to purchase energy drinks regardless of their socioeconomic level. The target audience has a fast pace of life, prioritizes work over other aspects of their life and, even if they’re stressed, considers such a motivation to work harder. That is why Boom Power was created, an energy drink that revives you and provides the extra energy you need for the moment. The project is divided into three parts: the research carried out for the creation of the brand, the creative proposal of Boom Power and the support of the media plan for the campaign with its respective graphic materials